(untitled) (Research, Society and Development, 2020)
In order to provide speed and accuracy in the design of hydraulic structures, several computational resources have been used in this activity. The objective of this research was to develop an application for Android® system designed to design and calculate the flow rate of canals of trapezoidal, rectangular, triangular and circular sections. We sought to create a tool that is easy to use for students and hydraulic engineering professionals, and, at the same time, capable of providing accurate results. The application was developed using the App Inventor 2 platform, being called DIM Canal. The application was developed in two stages. Initially, the presentation screens were developed. Subsequently, the algorithm with the routines for the execution of the tasks of each screen was developed. The calculations performed are based on the Manning formula, using the conventional and economic methods. At the end of the development, it was observed that the DIM Canal application allows the dimensioning of channels of different geometries, using the conventional and economical method. In addition to making it possible to calculate the flow of channels with known sections. The DIM channel features friendly interfaces and intuitive handling, being available on the Google Play Store, or through the link: https://play.google.com/store/apps/details?id=appinventor.ai_elton_ asmartins.DIM_CANAL_10_07_18_V2. The DIM channel can be used by designers in the field of hydraulic engineering and also by professors and engineering students, helping the teaching-learning process and improving the understanding of the observed phenomena.